Integral manifolds and the reduction principle for neutral functional-differential equations - Klevchuk, I.I. (Yuriy Fedkovych Chernivtsi National University, 2016)
We prove the reduction principle for investigating the stability of zero solution of a nonlinear differential equation of neutral type in the critical case. The problem is reduced to the investigation of the zero solution of an ordinary differential equation constructed by the method of integral manifolds.
Інтегральні многовиди і принцип зведення для диференціально-функціональних рівнянь нейтрального типу
Клевчук, І. (1). Інтегральні многовиди і принцип зведення для диференціально-функціональних рівнянь нейтрального типу. Bukovinian Mathematical Journal, 4(1-2). Retrieved from https://bmj.fmi.org.ua/index.php/adm/article/view/184
Keywords: neutral-type nonlinear differential equation; integral manifolds